Understanding staff turnover among Generation Y graduates in Singapore - OH, JING PING (2013)
It is estimated that Gen Y Singaporeans will make up 75% of the local workforce by 2025. The typical Gen Y worker is twice as likely to leave a company within one year of hire compared to other generation workers. Research has shown that employee turnover incurs financial costs which could range from 90%- 200% of an employee’s annual pay. Thus, this report aims to understand the Singapore Gen Y graduate employees’ inclination to change jobs, and provides specific recommendations to retain this group of employees. This is achieved through asking every 35 respondents to answer a questionnaire and interview designed around three Research Questions (1) What are the key antecedents influencing staff turnover among Gen Y graduates in Singapore? (2) How does Gen Y graduates in Singapore view job hopping based on their personal experiences? 3) What can HR practitioners/Managers/Organizations do to improve the retention of Gen Y graduates in Singapore? The results revealed Organizational Commitment and Psychological Contract Violations to have the most impact on staff turnover among Gen Y graduates in Singapore. Job Stress had the least impact on staff turnover. It is pertinent to have good HRM practices to ensure Organizational Justice among employees. In addition, Individual Differences pertaining to Demographic factors and Psychological Capital contributed to staff turnover among Gen Y graduates. Gen Y graduates perceive job hopping as to change jobs within one year or less, and view changing jobs every 2-3 years as a norm. They are likely to change jobs from age 27 onwards. They seek job variety and aspire to experience career progression. Gen Y graduates are happy when they receive recognition and fulfil challenging work.